PENERAPAN LAYANAN BIMBINGAN KLASIKAL DENGAN TEKNIK LEARNING TOGETHER SEBAGAI UPAYA MENINGKATKAN MOTIVASI BERPRESTASI DI SMAN 1 WEDI - Eka Dewi Sri Wahyuni (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2023)
Based on initial observations of the learning process, it was obtained data that class XII MIPA I students at SMAN 1 Negeri Wedi had a fairly low achievement motivation, this was indicated by a lack of student concentration when receiving lessons, the existence of teacher communication in learning activities that was not effective and a lack of understanding of students' self-concept about learning goals. Therefore, it is necessary to carry out a series of services provided by counselors, one of which is classical guidance services. The purpose of this service is to provide students with an understanding that increasing achievement motivation is very necessary. Classical guidance that will be carried out with the methodLearning Together. Based on the data on the research results in the first cycle stage, criterion A was 6% (2) of children, then increased to 16% (5) of children in cycle II. While in criterion B in cycle I, there were 59% (19) of children and rose again to 66% (21) of children in cycle II. While in criterion C in cycle I, there were 34% (11) children and decreased in cycle II to 19% (6) children. While criterion D in the stages of cycle I and cycle II did not meet this criterion. Meanwhile, criterion E was not found in either cycle I or cycle II.